2019
DOI: 10.1016/j.waojou.2019.100085
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of rural life on mite sensitization disappears among urban migrants in the South of Vietnam

Abstract: BackgroundRapid urbanization combined with rural migration to urban areas in southern Vietnam could be risk factors for allergen sensitization, contributing to chronic respiratory diseases (CRD). We aimed to evaluate the prevalence of mite sensitization and its relation to house dust characteristics among rural and urban native and migrating populations with CRD.MethodsRural (n = 19) and urban (n = 46) dwellings were defined on the basis of a home typology. Controls were western Belgian houses (n = 14). Beside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Exposure to dust mite allergens is a risk factor for clinical asthma in sensitized subjects. [12] The relationship between allergic asthma and intestinal permeability is a subject of research interest. An increase in the intestinal permeability may result in facilitating the entry of allergenic proteins from the intestinal lumen into the systemic circulation.…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to dust mite allergens is a risk factor for clinical asthma in sensitized subjects. [12] The relationship between allergic asthma and intestinal permeability is a subject of research interest. An increase in the intestinal permeability may result in facilitating the entry of allergenic proteins from the intestinal lumen into the systemic circulation.…”
Section: Resultsmentioning
confidence: 99%
“…Allergic asthma can be sparked by allergen sensitization in which house dust mites (HDM) are among the most prevalent indoor allergens [ 14 ]. Exposure to dust mite allergens is a risk factor for clinical asthma in sensitized subjects [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the prevalence of HDM sensitization in allergic patients living in urban areas were higher than those living in rural area in Vietnam [8,11], which is consistent with the reports from other Southeast Asia countries. Recently, Chu et al [51] showed that a high endotoxin concentrations in rural houses were associated with a lower risk of HDM sensitization.…”
Section: Indonesiamentioning
confidence: 99%